Sesquiterpenes from the Roots of Illicium jiadifengpi - Zhang, Guijie; Zhuang, Pengyu; Wang, Xiaojing; Yu, Shishan; Ma, Shuanggang; Qu, Jing; Li, Yong; Liu, Yunbao; Zhang, Yan; Yu, Dequan (Planta Medica, 2013)
Two new sesquiterpenes (1, 2) and two new sesquiterpene glycosides (3, 4) with a seco-prezizaane skeleton, three new allo-cedrane sesquiterpene glycosides (5–7), and a new acorane sesquiterpene (8) as well as 15 known analogues were isolated from the roots of Illicium jiadifengpi used for the treatment of rheumatoid arthritis. The structures of these compounds were elucidated by extensive spectroscopic analysis and chemical methods. The absolute configurations of compounds 5–7 were confirmed by CD experiments. The configuration of compound 8 was assigned by single-crystal X-ray crystallographic analysis and CD experiments. Compounds 4, 6, 7, 14, and 23 showed moderate antiviral activities against Coxsackie virus B3, and all compounds were inactive when evaluated for their cytotoxic activities against five human tumor cell lines and neuroprotection.
Keywords: Illicium jiadifengpi; Illiciaceae; seco-prezizaane sesquiterpene; allo-cedrane sesquiterpene glycoside; acorane sesquiterpene